Sensitivity to Geometric Detail in Fatigue Simulation of Electronic Components of Vehicles - Zoltán Z. Kovács; Ambrus Zelei (Engineering Proceedings)
Solder joints strongly determine the lifetime of electronic components subjected to temperature fluctuations. The lifetime predictions obtained by finite element analysis (FEA) are uncertain due to the significant variation in solder geometry. It is unclear how realistic a geometric model is needed for problems of impartial complexity. A balance must be found between modeling effort and simulation accuracy. Six geometric models of the solder joint of a gullwing lead were built with different complexity, from the simplest to the most realistic, including a realistic reference model obtained by the Surface Evolver simulation software. The FEA results considering linear elastic and plastic material models were compared for the different solder geometries. We conclude that manually created solder geometry is a sufficient alternative to physics-based realistic geometries.